Komunikasi Akademik, Regulasi Emosi, dan Kemampuan Berpikir Logis Mahasiswa FKIP Universitas Satya Wiyata Mandala,Nabire, Papua Tengah - Winda Woro Mahmudah; Jermanto Subeno Lasamahu; Debby Priscilla Hendrayani Supit; Julvani Ayuningsih Warsito (Pusat Riset dan Inovasi Nasional, 2025)
Logical thinking is a fundamental competence for prospective teachers, as it supports systematic reasoning and professional decision-making. This study aimed to analyze the relationship between academic communication and emotional regulation with the logical thinking skills of students at the Faculty of Teacher Training and Education, Universitas Satya Wiyata Mandala, Nabire, Papua Tengah. A quantitative correlational design was employed with 100 students selected through proportional random sampling. Data were collected using an academic communication questionnaire, an emotional regulation scale, and a logical reasoning test, and analyzed through Pearson correlation and multiple regression. The findings indicate that both academic communication and emotional regulation have positive and significant relationships with logical thinking skills, both partially and simultaneously. These results emphasize that logical thinking development in higher education requires the integration of cognitive, interpersonal, and emotional competencies.